(3QhVI GdYdeGA hfRgI GdaVdGAs - (3MSjf Hf jMji GdHNGQj GdRfOhSJj GdMfaj, CHh Ydjs
(3ChdgG (B:s
(3CeG MeOGddg GdcQje GdoeJYGd hGdUdGI Ydi fHjg eMeO hBdg NjQ Bd , OYGfj GdMGLI Edi Cf CcJH QhVI GdYdeGA hfRgI GdaVdGA s
(3BNQgG (B:s
(3jLYd eGcJHg NGdUkG dMVQJg hjQVi Yef WGdY aj gPG GdcJGH hGdYPQ Yf cQGe GdfGS ebHhd s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B928s
Keywords: (3GdJUha hGdBOGH GdTQYjIs